The Effect of Joint Hypermobility Syndrome on DOMS and Recovery Time - Nicole F Ostuni; Charles A Marinello; Taras Luzhnyy; Alexa Pawlikowski; Connor Vlasaty; Georgios Thomatos; Peter C Douris (North American Sports Medicine Institute, 2024)
# Background Previous research has reported that people with Joint Hypermobility Syndrome (JHS) and Ehlers-Danlos Syndrome (EDS) generally experience a high rate of muscular injury and pain. However, there is limited research comparing the recovery times and length of Delayed Onset Muscle Soreness (DOMS) in individuals with JHS to non-hypermobile individuals in response to exercise. # Hypotheses/Purpose The purpose of this study was to investigate JHS and its effects on DOMS and its recovery time. # Study Design Quasi-experimental, observational comparison # Methods Two groups including a hypermobile group (score >4 on Beighton Scale) and a non-hypermobile group all took part in five-second long standing eccentric bicep curls based using their one- repetition maximum (1-RM) of their dominant arm to failure in order to induce DOMS. Visual analog pain scale (VAS), McGill pain scale, resting arm angle, girth, and the pressure pain threshold, all domains of DOMS, were measured over a five-day period. Results were analyzed using ANOVA with time as the repeated factor. # Results Both groups experienced DOMS following the eccentric exercise. However, VAS reporting was significantly greater in the hypermobile group compared to the non-hypermobile group and there was a significant difference over time. However, other variables did not reveal any other significant findings between groups. # Conclusion Individuals with JHS may experience greater DOMS and require more time to recover between treatment sessions. Therapists need to be aware that patients with hypermobility may experience higher pain levels related to exercise, and they need to adjust treatment parameters appropriately. # Level of Evidence 2b